The exp(-φ(z))-expansion method for (3+1)-dimensional generalized Boiti-Leon-Manna-Pempinelli equation - Gu, Yongyi (IJRDO -JOURNAL OF MATHEMATICS, 2018)
In this paper, we apply the exp(-φ(z))-expansion method to obtain exact solutions of the (3+1)-dimensional generalized Boiti-Leon-Manna-Pempinelli equation, and then we give some computer simulations to illustrate our main results. Four types of exact solutions are obtained, which are hyperbolic, exponential, trigonometric and rational function solutions.